PMP exam prep all the help you need, from start to finish - Baca, Claudia; Safari eBooks ([United States?] : Addison-Wesley Professional, 2008)
"PMP Exam Prep Live Lessons presents information on the PMP/CAPM exam in an easily accessible, common-sense manner. This innovative series of video courses covers everything you need to successfully pass the PMP/CAPM exam. The product instructs on all PMP topics with vivid visual coverage and audio explanations from the author. The lessons have real-world examples that translate the exam topics into more easily understood concepts. The lessons also help students fill out the proper paperwork, build a study plan, and provides all of the necessary information to study for the PMP/CAPM exam. This Safari product guides PMP candidates through the six disciplines they need to study for the exam, and also provides access to an online sample exam readers can take to help them prepare for the certification test. Access to an online test is also provided to provide readiness feedback."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed Feb. 22, 2009).
Electronic reproduction.
Keywords: Project management; Electronic books